Multipolar interactions in Si sphere metagratings - E. Panagiotidis; E. Almpanis; N. Stefanou; N. Papanikolaou (Journal of Applied Physics, 2020)
A thorough theoretical study of the optical properties of periodic Si nanosphere arrays is undertaken, placing a particular emphasis on the synergy between multipolar, electric and magnetic, Mie resonances, which occur in high-refractive-index nanoparticles and can lead to a rich variety of phenomena ranging from perfect reflection to controlled diffraction. Systematic calculations using the layer-multiple-scattering method, which we properly extended to describe periodic arrays with many different scatterers per unit cell, in conjunction with finite-element simulations are presented. It is shown that rectangular arrays of pairs of Si nanospheres can efficiently diffract light in reflection or transmission mode at large angles as well as split light with minimum backreflection by properly adjusting the geometry of the structure. Our rigorous full-electrodynamic calculations highlight the importance of higher-order multipoles, which are not taken into account in the commonly employed dipole approximation, in the description of these effects.